# Solve each system by substitution. 3u+8=4v 24v=6-3u

*print*Print*list*Cite

### 1 Answer

To use substitution, you solve one of the equations for one of the variables; then you substitute the expression for that variable into the other equation.

3u+8=4v

24v=6-3u

If we solve the first equation for v we get :

`3/4u+2=v`

Now substitute `3/4u+2` in place of v in the second equation:

`24(3/4u+2)=6-3u`

`18u+48=6-3u`

`21u=-42==>u=-2`

Then `v=3/4u+2=3/4(-2)+2`

so `v=-3/2+4/2=1/2`

**The solution to the system is `u=-2,v=1/2` **

Checking we get `3u+8=3(-2)+8=2=4(1/2)=4v`

`24v=24(1/2)=12=6-(-6)=6-3(-2)=6-3u`